Ship or sheep? : An intermediate pronunciation course - Baker, Ann. (Cambridge : Cambridge University Press, 1981)
This book trains students to recognise and produce English sounds, and includes work on stress and pronunciation.
Keywords: English language -- Pronunciation; English language -- Textbooks for foreign speakers; English language